Pseudonyms for Cancer Registries - Pommerening, K.; Miller, M.; Schmidtmann, I.; Michaelis, J. (Methods of Information in Medicine, 1996)
In order to conform to the rigid German legislation on data privacy and security we developed a new concept of data flow and data storage for population-based cancer registries. A special trusted office generates a pseudonym for each case by a cryptographic procedure. This office also handles the notification of cases and communicates with the reporting physicians. It passes pseudonymous records to the registration office for permanent storage. The registration office links the records according to the pseudonyms. Starting from a requirements analysis we show how to construct the pseudonyms; we then show that they meet the requirements. We discuss how the pseudonyms have to be protected by cryptographic and organizational means. A pilot study showed that the proposed procedure gives acceptable synonym and homonym error rates. The methods described are not restricted to cancer registration and may serve as a model for comparable applications in medical informatics.
Keywords: Cancer Registry; Data Protection; Data Encryption; Pseudonyms; Record Linkage